Thrombolytic therapy and beta-adrenergic blockade in acute myocardial infarction : a prospective evaluation at Groote Schuur Hospital 1988-1990 - Green, Belinda K W (Division of Cardiology, 2018)
The advent of intravenous thrombolytic agents has revolutiontzed the management of patients with acute myocardial infarction and has dramatically altered the morbidity and mortality associated with this condition. The aims of this study in patients presenting with acute myocardial infarction and treated with thrombolytic agents are: 1. To evaluate the efficacy of thrombolytic agents used at Groote Schuur Hospital in terms of (a) patency of the infarct related artery; ( b) short and long-term mortality. 2. To assess the feasibility and safety of combining intravenous beta-adrenergic blockade with intravenous thrombolytic therapy in patients presenting with acute nyocardial infarction. 3. To assess the need for coronary angiography in all patients treated with thrombolytic agents for acute myocardial infarction. 4. To assess the effect on mortality of offering coronary angioplasty or coronary artery bypass grafting only to those patients manifesting spontaneous or inducible ischaemia post infarction.